Introducing Spiro‐locks into the Nitrogen/Carbonyl System towards Efficient Narrowband Deep‐blue Multi‐resonance TADF Emitters - Yu, You‐Jun; Feng, Zi‐Qi; Meng, Xin‐Yue; Chen, Long; Liu, Fu‐Ming; Yang, Sheng‐Yi; Zhou, Dong‐Ying; Liao, Liang‐Sheng; Jiang, Zuo‐Quan (Angewandte Chemie International Edition, 2023)
The current availability of multi‐resonance thermally activated delayed fluorescence (MR‐TADF) materials with excellent color purity and high device efficiency in the deep‐blue region is appealing. To address this issue in the emerged nitrogen/carbonyl MR‐TADF system, we propose a spiro‐lock strategy. By incorporating spiro functionalization into a concise molecular skeleton, a series of emitters (SFQ, SOQ, SSQ, and SSeQ) can enhance molecular rigidity, blue‐shift the emission peak, narrow the emission band, increase the photoluminescence quantum yield by over 92 %, and suppress intermolecular interactions in the film state. The referent CZQ without spiro structure has a more planar skeleton, and its bluer emission in the solution state redshifts over 40 nm with serious spectrum broadening and a low PLQY in the film state. As a result, SSQ achieves an external quantum efficiency of 25.5 % with a peak at 456 nm and a small full width at half maximum of 31 nm in a simple unsensitized device, significantly outperforming CZQ. This work discloses the importance of spiro‐junction in modulating deep‐blue MR‐TADF emitters. The various spiro‐locks were introduced into the nitrogen/carbonyl‐based multi‐resonance thermally activated delayed fluorescence (MR‐TADF) system via a designed synthetic route. The introduction of spiro‐locks increased molecular rigidity and suppressed intermolecular interactions. Thus, narrowband deep‐blue electroluminescence spectra and improved device efficiencies were achieved simultaneously.